Clownesque Poetics in Jules Laforgue's Moralités légendaires. (2nd January 2016) - Forrest, Jennifer
Abstract : In 1883, Jules Laforgue described his literary expression as clownesque. While this characterization generally suggests the figure of Pierrot to those familiar with the poet's Les Complaintes (1885) and L'Imitation de Notre-Dame la Lune (1886), it is clear from his Moralités légendaires (1887) that his poetics had evolved to embrace the circus performer (clown or acrobat) as a figure whose existential identity is ambiguously double, and to adapt the circus ring as a semantic space in which such impossible incompatibilities can emerge and be sustained. Most of the collection's nouvelles possess a few carefully chosen and placed circus-related words that signal moments of existential limbo in which the tales' characters become both themselves and their opposite. As with his mots-valise, whose individual components retain their distinctiveness, Laforgue creates characters whose dual natures establish textual space as that other arena in which the ontologically impossible paradoxically occurs.